Circulating tumor DNA: Opportunities and challenges for pharmacometric approaches - Ribba, Benjamin; Roller, Andreas; Helms, Hans-Joachim; Stern, Martin; Bleul, Conrad (Frontiers in Pharmacology, 2023)
Abstract/Introduction (perspective): Predicting long-term clinical benefit of anti-cancer drugs is notoriously difficult. Nevertheless, such predictions can play a key role in reducing the attrition rate of anti-cancer molecules in late phase clinical trials [1]. Recently, circulating tumor DNA (deoxyribonucleic acid) or ctDNA - which can be collected longitudinally - has been shown to hold additional predictive power to imaging-based markers of response [2]. Pharmacometric (PMX) approaches can take advantage of longitudinal measurements as demonstrated with tumor growth modeling approaches and - as such - represent an opportunity for ctDNA to inform new molecular entity (NME) clinical trial development with respect to identification of clinically most promising compounds, optimal sampling design, combination partners, and precision dosing. In this perspective - through the exploratory analysis of ctDNA data from nearly 500 cancer patients treated with checkpoint inhibitors and targeted therapies - we dissect the relationships between on-treatment ctDNA change over time from baseline and overall survival, clinical response and tumor size dynamics. We believe this effort is a required first step for further successful development of model-based approaches. The analysis also sheds light on interconnected challenges related to the specific nature of the data, associated variability, and complexity of underlying biology of ctDNA processes such as shedding, release and clearance [3] and their relationships with tumor size dynamics and treatment effects (see Figure 1, panel A).